Deconstructing Complex Multimorbidity in the Very Old: Findings from the Newcastle 85+ Study. (13th January 2016) - Collerton, Joanna; Jagger, Carol; Yadegarfar, Mohammad E.; Davies, Karen; Parker, Stuart G.; Robinson, Louise; Kirkwood, Thomas B. L.
Abstract : Objectives . To examine the extent and complexity of the morbidity burden in 85-year-olds; identify patterns within multimorbidity; and explore associations with medication and healthcare use. Participants . 710 men and women; mean (SD) age 85.5 (0.4) years. Methods . Data on 20 chronic conditions (diseases and geriatric conditions) ascertained from general practice records and participant assessment. Cluster analysis within the multimorbid sample identified subgroups sharing morbidity profiles. Clusters were compared on medication and healthcare use. Results . 92.7% (658/710) of participants had multimorbidity; median number of conditions: 4 (IQR 3–6). Cluster analysis (multimorbid sample) identified five subgroups sharing similar morbidity profiles; 60.0% (395/658) of participants belonged to one of two high morbidity clusters, with only 4.9% (32/658) in the healthiest cluster. Healthcare use was high, with polypharmacy (≥5 medications) in 69.8% (459/658). Between-cluster differences were found in medication count (p = 0.0001 ); hospital admissions (p = 0.022 ); and general practitioner (p = 0.034 ) and practice nurse consultations (p = 0.011 ). Morbidity load was related to medication burden and use of some, but not all, healthcare services. Conclusions . The majority of 85-year-olds had extensive and complex morbidity. Elaborating participant clusters sharing similar morbidity profiles will help inform future healthcare provision and the identification of common underlying biological mechanisms.